COMPARISON OF HEALTH LITERACY AMONG IRAQI WOMEN WITH DIFFERENT AGE GROUPS - AL-NEMA, ZENA MUDHAFER (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objectives: The objectives of the study were to compare the health knowledge of women of different age groups. To evaluate different methods for developing health literacy. Methods: A cross-sectional study was conducted from December 2014 to January 2016 in Baghdad, Iraq. All candidates were females, age ≥18 years, neither medical staff nor medical students. The sample was divided into two groups: Group A: Females aged18–45 years, Group B: Females aged >45 years. A comparison between the two groups regarding their health literacy and the source of information was made. Results: The final sample included 213 women, of them, there were 107≤45 years (Group A) and 106>45 years (Group B) women. Significant difference was found between both groups regarding the knowledge about the prevention of cholera where the accurate answers were 46.7% in Group A versus 80.1% in Group B. The main source of information for both groups was the personal experience. However, internet was used more (42%) by the younger women (Group A), and television was used more (52.8%) by the older women (Group B). Conclusion: Young women had a better literacy on common medical problems, but the old showed overall limited health literacy. Pharmacists, physicians, and activities of the Ministry of Health played an impotent role in health literacy in the old women.